Post a New Question

math

posted by .

y^2-6y=-7

x^2=8x-41

(4x-1)(2x+6)=3x

45-t^2=0

(3x-6)^2=33

  • math -

    They want you to solve for the unknown variable. You need to rewrite the equation in quadratic form
    ax^2 + bx + c = 0, first of all.

    y^2 -6x = -7 can be rewritten
    y^2 -6x +7 = 0

    Use the quadratic formula to solve.
    http://www.purplemath.com/modules/quadform.htm

    y = [6 +/-sqrt(36-28)]/2
    = 3 +/- sqrt2

    You do the others; someone will check your work if you make the effort.

Answer This Question

First Name
School Subject
Your Answer

Related Questions

More Related Questions

Post a New Question